What's working memory to do with it? A case study on teenagers - Price, Andrew; Oliver, Mary; Joshua, McGrane (Australian Science Teachers Association, 2015)
Effective teachers recognise that as their students grow, the way in which their students learn changes. This is related to different developmental stages of the brain that occur as a child becomes an adult. This article discusses the concept of working memory and explores how working memory changes during adolescence. The research presented here used an approach to measuring working memory using electroencephalography (EEG) to examine differences in the capacity for using working memory between older and younger adolescent students at a school in Western Australia. The differences in the neurological processes related to working memory in adolescents of different ages were examined with implications for teachers in secondary schools.